HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TUBERCULOSIS PARU RELAPSE DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015 - Mestiana Br. Karo (Elisabeth Health Jurnal, 2016)
Tuberculosis is a contagious infectious disease caused by mycobacterium tuberculosis. Pulmonary tuberculosis relapse is pulmonary tuberculosis patients who relapse or recurrent back. Support family also processes that occur throughout life, in which the source and type of support affects the life cycle stage family. Goal: This study aimed to identify the relationship with the family support medication adherence in patients with pulmonary tuberculosis relapse in Santa Elisabeth Hospital Medan. Methods: This study Using cross sectional research design, sampling is done by total sampling method with a total sample of 25 respondents. Result: The results of support family size of 52,0% and compliance drink pulmonary tuberculosis drug relapse 52,0%. Conclusion: Di suggest to support compliance is to involve all family members as supervisors drink medication after discharge from the hospital, assisting the patient to consul back and provide health education of patients taking the drug and dosage schedule is recommended by health professionals.